JUAN DE MAIRENA (1936): HIPÓSTASIS DEL APÓCRIFO MODERNISTA (Analele Universităţii Bucureşti. Limbi şi Literaturi Străine, 2025)
The creation of Antonio Machado’s apocryphal personalities, the best known of which are Abel Martin and Juan de Mairena, represents a central part of his poetic thought. Our paper aims to explore the personality of Juan de Mairena as reflected in the1936 prose volume, Sentencias, donaires, apuntes y recuerdos de un profesor apócrifo. The falsification of identity and the appropriation of an independent body of work separate from what the real author publishes under his real name offers freedom ofopinion and a special strategy to debate controversial topics related to artistic creation, philosophy, religion and politics. We shall argue that for Machado the apocrypha is more than an aesthetic and literary motif, that it represents a way of establishing acomplex and problematic relationship with reality.
Keywords: Antonio Machado; Mairena; apocrypha; heteronym; miscellanea